Pengaruh Toxic Relationship dan Overthinking dalam Pacaran Terhadap Kecemasan Berlebih (anxiety disorder) pada Kelas X SMA - Richie Annisa Cikal; Richma Hidayati; Santoso Santoso (Journal of Society Counseling, 2026)
Anxiety is a vague feeling of fear or apprehension, and it is a response to external or internal stimuli that can manifest as behavioral, emotional, cognitive, and physical symptoms (Swarjana, 2021). This study aims to analyze the effect of toxic relationships and overthinking in romantic relationships on anxiety disorders among tenth-grade students of SMA Negeri 1 Kudus. This research used a quantitative approach with the multiple linear regression method. The study population was 385 students from 11 classes, and a sample of 196 students was drawn using cluster sampling based on the Slovin formula. The instrument was a Likert scale questionnaire validated with 34 valid items out of 35 tested on 36 respondents. Cronbach's Alpha values were 0.867 (toxic relationship), 0.827 (overthinking), and 0.865 (anxiety disorder). Data were analyzed using IBM SPSS Statistics 23. The Kolmogorov-Smirnov normality test yielded Asymp.Sig. 0.200 > 0.05. The multicollinearity test showed Tolerance 0.902 and VIF 1.108. Glejser heteroscedasticity test showed sig. values of 0.145 and 0.548 for both variables. Partial t-test results: (1) toxic relationship significantly affects anxiety disorder (t = 2.035, sig. = 0.043); (2) overthinking significantly affects anxiety disorder (t = 6.386, sig. = 0.000). The F-test showed F = 29.401, sig. = 0.000. The coefficient of determination R² = 0.234, indicating 23.4% of anxiety disorder variance is explained by both predictors.